Modeling of mechanical behavior of cork in compression (Fracture and Structural Integrity, 2020)
The present work consists of a contribution in modeling the mechanical behavior of cork in compression. For this purpose, compression tests are performed in the non-radial direction on high density reproduction cork samples. Cork shows stress-strain curves, typical of cellular materials, characterized by an elastic slope followed by an important plateau corresponding to buckling of cells; and finally hardening due to the densification of the material. Two behavior models are proposed to represent this behavior. A trilinear model in which each slope represents one of the three domains and whose parameters are identified directly from the stress-strain curves. A more nonlinear model corresponding to a third-order polynomial whose parameters are identified by means of a polynomial regression. Test-model comparisons reveal little relevance of the results given by the trilinear model whereas a very good consistency is observed for the results given by the nonlinear model.
Keywords: Cork; Compression; Behavior model; Parameters identification; Stress-strain